Green Pathway in Utilizing CO2 via Cycloaddition Reaction with EpoxideA Mini Review - Kunlanan Kiatkittipong; Muhammad Amirul Amin Mohamad Shukri; Worapon Kiatkittipong; Jun Wei Lim; Pau Loke Show; Man Kee Lam; Suttichai Assabumrungrat (My University, 2020)
Carbon dioxide (CO2) has been anticipated as an ideal carbon building block for organic synthesis due to the noble properties of CO2, which are abundant renewable carbon feedstock, non-toxic nature, and contributing to a more sustainable use of resources. Several green and proficient routes have been established for chemical CO2 fixation. Among the prominent routes, this review epitomizes the reactions involving cycloaddition of epoxides with CO2 in producing cyclic carbonate. Cyclic carbonate has been widely used as a polar aprotic solvent, as an electrolyte in Li-ion batteries, and as precursors for various forms of chemical synthesis such as polycarbonates and polyurethanes. This review provides an overview in terms of the reaction mechanistic pathway and recent advances in the development of several classes of catalysts, including homogeneous organocatalysts (e.g., organic salt, ionic liquid, deep eutectic solvents), organometallic (e.g., mono-, bi-, and tri-metal salen complexes and non-salen complexes) and heterogeneous supported catalysts, and metal organic framework (MOF). Selection of effective catalysts for various epoxide substrates is very important in determining the cycloaddition operating condition. Under their catalytic systems, all classes of these catalysts, with regard to recent developments, can exhibit CO2 cycloaddition of terminal epoxide substrates at ambient temperatures and low CO2 pressure. Although highly desired conversion can be achieved for internal epoxide substrates, higher temperature and pressure are normally required. This includes fatty acid-derived terminal epoxides for oleochemical carbonate production. The production of fully renewable resources by employment of bio-based epoxy with biorefinery concept and potential enhancement of cycloaddition reactions are pointed out as well.
Keywords: Organic Synthesis; Carbon dioxide utilization in catalysis